THE EFFECT OF LEARNING DISCIPLINE ON STUDENT LEARNING OUTCOMES OF ISLAMIC HISTORY COURES IN IT AL ISLAMIYYAH BOARDING SCHOOL VOCATIONAL SCHOOL - Lingling Parwati; Nadia Rista (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
This study intends to determine whether there is a disciplinary effect between the influence of learning discipline on the learning outcomes of class X students at SMK IT Islamiyyah Boarding School. The sample used is 50 students. This type of research used is quantitative assosciative. The method used is a descriptive survey. Which uses a saturade sample or a census sample to determine the sample if the entire population is sampled. Research data (1) Linear Regression Equation 38.309 + 0.554 X. (2) Learning discipline affects student learning outcomes in Islamic history subjects in class X IT Al Islamiyyah Boarding School, the p-value is less than 0.05. It can be interpreted that the learning outcomes of Islamic history at SMK IT Al Islamiyyah Boarding School class X are positively influenced by the field of study. (3) From the significant test of the regression equation, thit = 6.033, p-value = 0.000 < 0.05 or Ho is rejected. Therefore, using simple Y or X regression, it is significant that learning discipline affects learning outcomes, or learning discipline affects Islamic history learning outcomes. (4) Test the correlation coefficient (rxy) = 0.657 and fthit (Fchange) = 36,398 and p-value = 0.000 < 0.05. Therefore the correlation coefficient of X and Y is significant. The coefficient of determination is R-Square = 0.431, meaning that 43.1% of the variation in Islamic history learning outcomes can be influenced by learning outcomes.